2021
DOI: 10.3389/fpsyg.2021.664554
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Science, Perceived Vulnerability to Disease, and Adherence to Pharmacological and Non-pharmacological COVID-19 Recommendations

Abstract: Protection motivation theory (PMT) is a theoretical framework informative for understanding behavioral intentions and choices during exceptional and uncommon circumstances, such as a pandemic of respiratory infectious disease. PMT postulates both the threat appraisal and the coping appraisal as predictors of health behaviors. Recent advances in the field of behavioral immune system (BIS) research suggest that humans are equipped with a set of psychological adaptations enabling them to detect the disease-threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…For example, civic attitudes (Roma et al, 2020) and trust in science and scientists (Dohle et al, 2020;Hromatko et al, 2021) are found to be positively related to adherence to COVID-19 protective measures. However, while some previous research, consistent with this study, show that education is negatively related to beliefs in conspiracies (Hornik et al, 2021), some other show that education is not a significant predictor (Hromatko et al, 2021;Karić and Mededović, 2021) or is even negatively related to compliance to protective measures (Roma et al, 2020). These results suggest that the relationship of education with belief in conspiracies and adherence to protective measures is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…For example, civic attitudes (Roma et al, 2020) and trust in science and scientists (Dohle et al, 2020;Hromatko et al, 2021) are found to be positively related to adherence to COVID-19 protective measures. However, while some previous research, consistent with this study, show that education is negatively related to beliefs in conspiracies (Hornik et al, 2021), some other show that education is not a significant predictor (Hromatko et al, 2021;Karić and Mededović, 2021) or is even negatively related to compliance to protective measures (Roma et al, 2020). These results suggest that the relationship of education with belief in conspiracies and adherence to protective measures is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…PMT has been applied to explain the motivation to adopt preventive behaviors [ 41 , 42 , 43 , 44 , 45 , 46 ] and to get vaccinated against COVID-19 [ 31 , 44 , 47 , 48 ]. Cross-sectional studies have revealed that perceived severity of and vulnerability to COVID-19, self-efficacy to adopt preventive behaviors, and response efficacy of preventive behaviors are positively associated with the intention to adhere to recommended protective behaviors against COVID-19 [ 41 , 42 , 43 , 44 , 45 ]. A follow-up study demonstrated that perceived severity and response efficacy can predict the adoption of preventive behaviors against COVID-19 [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies have revealed that perceived severity of and vulnerability to COVID-19, self-efficacy to adopt preventive behaviors, and response efficacy of preventive behaviors are positively associated with the intention to adhere to recommended protective behaviors against COVID-19 [ 41 , 42 , 43 , 44 , 45 ]. A follow-up study demonstrated that perceived severity and response efficacy can predict the adoption of preventive behaviors against COVID-19 [ 44 ]. Moreover, research has revealed that the perceived severity of COVID-19 [ 46 ], response and cost efficacy of vaccination [ 44 , 48 ], and receiving an influenza vaccine [ 31 ] are associated with the motivation to receive COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the perceived severity and vulnerability are high, and the perceived rewards are low, there is a stronger motivation for engagement in health-promoting behaviors [ 15 ]. In the previous studies about preventive measures of COVID-19, Yazdanpanah et al [ 27 ] and Hromatko et al [ 28 ] reported that perceived vulnerability produced a positive and significant impression on preventive behaviors. However, in our study, a negative association was observed between perceived vulnerability and preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%